RON Receptor Tyrosine Kinase in Tumorigenic Stemness as a Therapeutic Target of Antibody-drug Conjugates for Eradication of Triple-negative Breast Cancer Stem Cells - Suthe, Sreedhar R.; Yao, Hang-Ping; Weng, Tian-Hao; Wang, Ming-Hai (Current Cancer Drug Targets, 2023)
Background: Cancer stem-like cells in triple-negative breast cancer (TNBC-SLCs) are the tumorigenic core for malignancy. Aberrant expression of the RON receptor tyrosine kinase has implications in TNBC tumorigenesis and malignancy. Objective: In this study, we identified the RON receptor as a pathogenic factor contributing to TNBC cell stemness and validated anti-RON antibody-drug conjugate Zt/g4-MMAE for eradication of RONexpressing TNBC-SLCs. Methods: Immunofluorescence and Western blotting were used for analyzing cellular marker expression. TNBC-SLCs were isolated by magnetic-immunofluorescence cell-sorting techniques. Spheroids were generated using the ultralow adhesion culture methods. Levels of TNBC-SLC chemosensitivity were determined by MTS assays. TNBC-SLC mediated tumor growth was determined in athymic nude mice. The effectiveness of Zt/g4-induced RON internalization was measured by immunofluorescence analysis. Efficacies of Zt/g4-MMAE in killing TNBC-SLCs in vitro and in eradicating TNBC-SLCmediated tumors were determined in mouse models. All data were statistically analyzed using the GraphPad Prism 7 software. Results: Increased RON expression existed in TNBC-SLCs with CD44+/CD24- phenotypes and ALDH activities and facilitated epithelial to mesenchymal transition. RON-positive TNBC-SLCs enhanced spheroid-formatting capability compared to RON-negative TNBC-SLCs, which were sensitive to small molecule kinase inhibitor BMS-777607. Increased RON expression also promoted TNBC-SLC chemoresistance and facilitated tumor growth at an accelerated rate. In vitro, Zt/g4-MMAE caused massive TNBC-SLC death with an average IC50 value of 1.56 μg per/ml and impaired TNBC cell spheroid formation. In mice, Zt/g4-MMAE effectively inhibited and/or eradicated TNBC-SLC mediated tumors in a single agent regimen. Conclusion: Sustained RON expression contributes to TNBC-SLC tumorigenesis. Zt/g4-MMAE is found to be effective in vivo in killing TNBC-SLC-mediated xenograft tumors. Our findings highlight the feasibility of Zt/g4-MMAE for the eradication of TNBC-SLCs in the future.
Keywords: cancer stem cell